EFFECT OF STUDENTS DISPOSITION ON THE CHOICE OF ACCOUNTING AS A SUBJECTS IN PRIVATE SECONDARY SCHOOLS IN CALABAR SOUTH LOCAL GOVERNMENT AREA OF CROSS RIVER STATE, NIGERIA - EGU USANG INAH; GLORY TOCHUKWU AKAH; JOHN OGAR–ABANG OYONG (International Studies Journal)
This study adopted ex-post facto design to examine the effect of students’ disposition on the choice of accounting as   a subject in private secondary schools in Calabar South Local Government Area of Cross River State, Nigeria.  It was guided by two research questions and two null hypotheses. A sample of sixty (60) SS2 Accounting students were selected from private secondary schools using the    proportionate and simple random sampling techniques. One instrument titled “Students disposition and  choice  of  accounting  subjects  Questionnaire (SDCASQ) was   used for data collection.  The reliability of the questionnaire established using Cronbach Alpha ranged from .85 to .90. The hypotheses were tested using Simple Linear  Regression Analysis  at .05 level of significance. The findings of the study revealed that students personal  interest, students’ perceived  competence   significantly  influence the choice  of accounting  subjects in Calabar  South  of Cross River State, Nigeria . It was  concluded   that     the choice  of accounting   subject depend on    students personal  interest and students’ perceived  competence . Based  on the conclusion  of the study, it  was  recommended  that school  administrators   should  develop educational workshops and mentorship programs that build students' competencies, interest  in accounting   that can help demystify the subject and enhance their confidence in their abilities.